2012
DOI: 10.4103/0019-5359.114198
|View full text |Cite
|
Sign up to set email alerts
|

Anemia among adolescent girls in Shimla hills of north India: Does BMI and onset of menarche have a role?

Abstract: We observed a low prevalence of anemia among adolescent girls. We recommend that adolescents be screened periodically for anemia and multi-sectoral, community-based approach be adopted to combat this serious public health issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 6 publications
2
23
1
2
Order By: Relevance
“…Our findings are consistent with the studies done by Rajaratnam J et al, Sharda S et al, Goyle A, Prakash S and Chaudhary SM et al 7,[13][14][15] Gupta A, Paraskar A et al conducted study in1596 adolescent girls of age (10-19 years). 16 It was seen that among the anaemic adolescent girls, 77.3% had mild anaemia, 21.9% had moderate anaemia, and 0.9% had severe anaemia. Present study differs from the study done by Rawat CMS et al who reported 19.0 % mild, 14.1% moderate and 1.4% severe anaemia in adolescent girls.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…Our findings are consistent with the studies done by Rajaratnam J et al, Sharda S et al, Goyle A, Prakash S and Chaudhary SM et al 7,[13][14][15] Gupta A, Paraskar A et al conducted study in1596 adolescent girls of age (10-19 years). 16 It was seen that among the anaemic adolescent girls, 77.3% had mild anaemia, 21.9% had moderate anaemia, and 0.9% had severe anaemia. Present study differs from the study done by Rawat CMS et al who reported 19.0 % mild, 14.1% moderate and 1.4% severe anaemia in adolescent girls.…”
Section: Discussionmentioning
confidence: 94%
“…The National Family Health Survey-3 (NFHS-3) data suggests that anaemia among adolescent girls (15)(16)(17)(18)(19) years) is 56 percent. 1 Sample size (n) was calculated with the help of formula as below.…”
Section: Sample Sizementioning
confidence: 99%
“…The findings of the study are consistent with the several previous studies. 16,28,29 While some earlier studies indicated that the body mass index was associated with anaemia and reported that the prevalence was high in underweight girls. 11,30 This study found that the prevalence of anaemia was slightly high in late adolescents as compared to in the early adolescent's girls which also observed in previous studies that age of the adolescent girls shows a significant relation with the prevalence of anaemia, it may be attributed to started of menarche time.…”
Section: Discussionmentioning
confidence: 99%
“…11,30 This study found that the prevalence of anaemia was slightly high in late adolescents as compared to in the early adolescent's girls which also observed in previous studies that age of the adolescent girls shows a significant relation with the prevalence of anaemia, it may be attributed to started of menarche time. 28,31 However, some studies also indicated that there is no significant association of age of adolescent girls and anaemia. [32][33][34] On multiple regressions analysis shows that the age of adolescent, education of adolescent, religion, caste, income strata and region of residence is found to be associated with anaemia in adolescent girls which indicated in several earlier studies.…”
Section: Discussionmentioning
confidence: 99%
“…2 They are four time risk of developing anemia compared to developed countries In India by 1970 3 the government of India has launched a national nutritional programme for anemia i.e anemia prophylaxis program were it was targeted more for the vulnerable eligible couples of pregnant mothers and many agencies came forward for this program for strengthening the strategies they wanted to get adopted for control of anemia in rural area but there was least contribution in the urban school children according to the program.Though the urban government school children comes under the preview of urban primary care region, on every Thursdays there will be an school health activities but unfortunately there is a lack of services to rectify and halt the progress of disorder among these children. 4 Adolescent school children are exposed to multiple dietary factors; they are eating most commonly available foods like rice porridge, snacks, locally available sweets from the neighboring shops and finally they land up in multiple factors of having worm infestations and there by leading to anemia. There are multiple factors can be predicted for the occurrence of the disease and clinical manifestation.…”
Section: Introductionmentioning
confidence: 99%